Buried in shamrocks - Mathews, Lisa Q. (Mathews, Lisa Q. Irish bed & breakfast mystery., 2026)
Kate and her daughters, Maeve and Bliz, are back in Shamrock, Massachusetts, and Kate faces a big decision: Should they move back to their hometown for good? As she contemplates the idea, all the businesses in town, including her family's B&B, the Buckley House, are busy preparing for the annual Great Shamrock Fair in hopes of luring back tourists after a murder during St. Patrick's Week. But when Kate's ex, Ian, arrives in town from Ireland to perform with his band at the festival and his new fiancée, Fallon, is found dead at the fairgrounds, any chance of a fun and peaceful family summer goes up in green smoke. Much as she wants nothing to do with her ex, Kate knows Ian is innocent. Amid the swirl of activity in town and her sister Colleen's determination to keep the annual Miss Shamrock contests alive, Kate enlists her devastated eldest daughter and her father, the former Shamrock police chief, to help her unwind the trail of evidence. With clues-and danger-piling up, can Kate find Fallon's true killer and save her ex, before the Great Shamrock Fair and the town's chances for a summer full of green go bust?